PROCEDURE FOR ORGANIZING, MAINTAINING AND ACCOUNTING FOR INTERBANK SETTLEMENTS - Baltabaev Makhmud Tashpulatovich (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This article examines one of the leading factors ensuring the stability of the banking system in modern economic conditions - the mechanisms for organizing interbank settlements, the procedure for conducting them and the methodology for reflecting them in accounting. The economic analysis of the relationship between payment flows carried out through the representative accounts and clearing systems of the Central Bank, real-time gross settlements (RTGS), and Nostro and Vostro accounts is carried out. At the end of the study, practical proposals are put forward to reduce liquidity risks in interbank payment systems and improve the digitalization of settlement operations.
Keywords: Keywords: interbank settlement, correspondent account, Nostro, Vostro, Central Bank, clearing, payment system, accounting, liquidity risk.